Application of molecular epidemiological methods to investigate strains of salmonella enterica serovar enteritidis in South Africa - Muvhali, Munyadziwa (My University, 2017)
In South Africa, Salmonella Enteritidis has become a significant pathogen and the numbers of cases reported to the Centre for Enteric Diseases (CED) have increased. Pulsed-field gel electrophoresis (PFGE) is a primary for molecular subtyping of Salmonella. However, this technique has poor discrimination for serotypes with high homogeneity such as Salmonella Enteritidis. Multi-locus variable-number tandem-repeats analysis (MLVA) has shown higher discriminatory power for Salmonella Enteritidis compared to PFGE. In this study, MLVA was used to investigate the molecular epidemiology and relatedness of human Salmonella Enteritidis strains from Gauteng and Western Cape, South Africa. Furthermore, MLVA was also used to investigate the relatedness of human and non-human Salmonella Enteritidis strains. MLVA included analysis of five VNTR loci, with varying degrees of diversity. A total of 1221 human isolates and 43 non-human isolates were included in the study. Eighty-six MLVA profiles were obtained; MLVA profiles 7, 21, 22 and 28 were the predominant MLVA profiles. MLVA profile 28 was the most common MLVA profile amongst both the human and non-human isolates. Isolates had low prevalence of antimicrobial resistance, however sulfamethoxazole resistance was notable amongst both the human (348; 29%) and non-human (10; 23%) isolates. During the study period, seven Salmonella Enteritidis outbreaks were investigated from six provinces and isolates from each individual outbreak showed an identical MLVA profile. MLVA was shown to be a successful molecular subtyping tool for Salmonella Enteritidis, for both surveillance purposes and outbreak investigations. Salmonella Enteritidis strains circulating within the human and non-human population were clonal. The study emphasizes the need for the one health approach, in order to curb the spread of Salmonella Enteritidis in South Africa.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2017
Keywords: Molecular Epidemiology Salmonella Enteritidis